DIALECTAL AND REGIONAL VARIANTS OF COLOR TERMS: A COMPARATIVE ANALYSIS (Ustozlar uchun, 2026)
Color terminology is among the most culturally embedded and linguistically variable domains of the lexicon. While the basic color categories across languages have been extensively studied since Berlin and Kay's landmark work, far less attention has been devoted to intra-language variation -the ways in which speakers of the same language use different color terms depending on their regional background, social group, or dialectal community. This article presents a comparative analysis of dialectal and regional variants of color terms within single languages, drawing on examples from English, Spanish, Arabic, and Russian.